2015
DOI: 10.1016/j.cpr.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

A resilience framework for promoting stable remission from depression

Abstract: A significant proportion of people in remission from depression will experience a recurrence of depression. One theoretical mechanism for this recurrence is that with each additional episode of depression, people become more sensitive to the deleterious effects of less powerful stressors. We propose that research on resilience -the ability to adapt to and recover from stress -can inform interventions to prevent recurrence in people in remission. We conceptualize resilience as a dynamic process that may be defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
126
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 154 publications
(145 citation statements)
references
References 126 publications
11
126
0
1
Order By: Relevance
“…This indicates the importance of directly targeting resilience next to focusing on specific vulnerabilities. At the clinical level, it is interesting to note that the central role of resilience also parallels an increased interest in treatments that focus on resilience (Garland et al, 2010;Geschwind et al, 2011;Keng et al, 2011;Waugh and Koster, 2015). Indeed, our findings indicate that patients may benefit from interventions targeting resilience mechanisms.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…This indicates the importance of directly targeting resilience next to focusing on specific vulnerabilities. At the clinical level, it is interesting to note that the central role of resilience also parallels an increased interest in treatments that focus on resilience (Garland et al, 2010;Geschwind et al, 2011;Keng et al, 2011;Waugh and Koster, 2015). Indeed, our findings indicate that patients may benefit from interventions targeting resilience mechanisms.…”
Section: Discussionsupporting
confidence: 63%
“…For instance, previous studies have shown that depression is associated with impaired stress-and emotional reactivity (Burke et al, 2005;Bylsma et al, 2008), which may continue during remission (e.g., O'Hara et al, 2014). In line with these findings, Waugh and Koster (2015) argue that stress recovery, positivity or promotion, and flexible application of coping responses -among other intra-or interpersonal factors contributing to resilience -may play an important role in preventing recurrence of depressive symptoms (but also see Southwick et al, 2005). These factors match the operationalization of resilience in this study, in line with Wagnild (2009), referring to concepts such as optimism, effectively coping with adversity, and flexibility.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations